H3.1K27me1 maintains transcriptional silencing and genome stability by preventing GCN5-mediated histone acetylation. Issue 4 (13th January 2021) - Dong, Jie; LeBlanc, Chantal; Poulet, Axel; Mermaz, Benoit; Villarino, Gonzalo; Webb, Kimberly M; Joly, Valentin; Mendez, Josefina; Voigt, Philipp; Jacob, Yannick
Abstract: Epigenetic mechanisms play diverse roles in the regulation of genome stability in eukaryotes. In Arabidopsis thaliana, genome stability is maintained during DNA replication by the H3.1K27 methyltransferases ARABIDOPSIS TRITHORAX-RELATED PROTEIN 5 (ATXR5) and ATXR6, which catalyze the deposition of K27me1 on replication-dependent H3.1 variants. The loss of H3.1K27me1 in atxr5 atxr6 double mutants leads to heterochromatin defects, including transcriptional de-repression and genomic instability, but the molecular mechanisms involved remain largely unknown. In this study, we identified the transcriptional co-activator and conserved histone acetyltransferase GCN5 as a mediator of transcriptional de-repression and genomic instability in the absence of H3.1K27me1. GCN5 is part of a SAGA-like complex in plants that requires the GCN5-interacting protein ADA2b and the chromatin remodeler CHR6 to mediate the heterochromatic defects in atxr5 atxr6 mutants. Our results also indicate that Arabidopsis GCN5 acetylates multiple lysine residues on H3.1 variants, but H3.1K27 and H3.1K36 play essential functions in inducing genomic instability in the absence of H3.1K27me1. Finally, we show that H3.1K36 acetylation by GCN5 is negatively regulated by H3.1K27me1 in vitro. Overall, this work reveals a key molecular role for H3.1K27me1 in maintaining transcriptional silencing and genome stability in heterochromatin by restricting GCN5-mediated histone acetylation in plants. Abstract : The histone post-translational modification H3.1K27me1 maintains transcriptional silencing and genome stability by preventing histone acetylation mediated by the histone acetyltransferase GCN5.